Using Low Level Laser (LLL for Treatment of Infected Mice with Carcinoma by Activating the Lymph Node Action without Drugs - Khaleel, A.Z.; Albir, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Regional immune response with mammary gland carcinoma was studied statistically. However, the prognostic value remains conflicting. Thirty mice were used in this study which infected were with mammary gland carcinoma. The tumor size of the animals under study were measured before and after laser irradiation by using a vernier and compared these results were with that of non irradiated animals with laser (control group) The aim of this study was to evaluate the effect of low level laser therapy (LLLT) on increasing the response of immune system by stimulating the lymph node action to decrease the cancer cell activity and then decreasing the tumor size of an infected mice. The results of the gross observations showed enlargement in the irradiated lymph node in comparison with that of non irradiated ones. It could be said that the enlargement which occurred to this lymph node proved that there was an increase in immune response by using laser stimulation. From this study, it can be concluded that the LLLT was an efficient tool in stimulating the defense cells found in the lymph node that attack the cancer cells locally. The result of this phenomenon demonstrates the decrease of the tumor size of the irradiated infected mice Introduction Lymph nodes are encapsulated spherical or kidney-shaped organs. The nodes are found in the axilla and the groin, along the great